A Qualitative Study on Pre-performance Routines of Diving: Evidence From Elite Chinese Diving Athletes - Yao, Qiang; Xu, Feng; Lin, Jiabao (Frontiers in Psychology, 2020)
Pre-performance routines (PPRs) are essential motor skills prior to a competition for athletes. But we believe that a specific kind of sport has its own PPRs. Using a qualitative research design, this study conducted in-depth interviews with 14 elite Chinese athletes in competitive diving and their coaches as well as observed and analyzed the behaviors of 13 athletes during diving competitions. The results showed that the divers’ PPRs were constituted of four components (psychological skills, pace setting, mastering competition progress, and behavioral strategies), which could be divided into 20 core categories, with the entire diving process divided into three sections and ten stages, including 13 subcategories in off-platform, 12 subcategories in on-platform and the diving stage. Thus, patterns in the PPRs for divers were established and a clear and comprehensive picture of the diving process, as well as the psychological characteristics and behavioral patterns of athletes during the process, were obtained. The findings entail implications for developing PPRs for diving athletes and future studies on PPRs in other competitive diving and other sports.